Information systems applied to transport improvement (2013)
Transport is one of the most relevant elements for the competitiveness of companies and cities. An inadequate transportation system generates high costs and low customer service levels, which ultimately produces a negative economic impact for both. This article presents an overview of the technology tools that are part of the Intelligent Transportation Systems (ITS) used to improve the performance and safety of transport, not only of cargo but also of passengers, in different modes such as air, maritime, rail and road. This article begins with a description of ITS, followed by the presentations of their benefi ts and, fi nally, it presents a review of the different tools for ITS.